Vienų motinų šeimos Lietuvos šeimos įstatymų kontekste - Skubiejutė, Greta (Socialinė teorija, empirija, politika ir praktika, 2020)
The main issue analyzed in the paper is policy design and its outcome on the social construction of single mother families and its effect on their wellbeing and life opportunities. Literature review and qualitative legislation documents analysis have been conducted to demonstrate how single mothers are perceived and treated in the context of social policy in Lithuania. The main findings of the paper show that in Lithuania, social policy is concentrated on controlling demography and therefore promotes traditional families and multi-child families. Meanwhile, single mother families are rather neglected and are not recognized by family policy as a group of a specific importance.
Keywords: vienų motinų šeimos; socialinė politika; šeimos politika